Stem Cell Banking: A Precious Gift to a Child from Parents - Sharma, Dr. Nidhi (Academia Anatomica International, 2017)
Stem cells are considered as the master cells that have the capability to self-renew, multiply rapidly and transform into any other type of cell. In the recent era, collection of stem cells from umbilical cord blood is becoming popular. Umbilical cord blood is defined as the blood that remains in the umbilical vein and placenta at the time of birth.